2016
DOI: 10.1097/md.0000000000004776
|View full text |Cite
|
Sign up to set email alerts
|

The optimal dose of dexmedetomidine added to an sufentanil-based analgesic regimen for postoperative pain control in spine surgery

Abstract: Postoperative spinal patients remain a challenge for provision of postoperative analgesia. Patient-controlled intravenous analgesia (PCIA) is a major method in reducing the severe pain after the surgery in our institution, but some adverse effects prevent the use of adequate dosage opioids.This study was determined using the probit analysis to investigate the optimal dose of dexmedetomidine (DEX) infusion for postoperative analgesia combined with sufentanil (SUF) in spine surgery.The dose of DEX needed to prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…A wider therapeutic index in sufentanil has been demonstrated compared with other commonly used opioids for PCIA, and sufentanil is not processed into active metabolites [ 24 , 25 ]. Also, the optimal dose of dexmedetomidine combining with sufentanil is vital and clinically the analgesic and sedation is satisfied maximumly, and the consumption of sufentanil is reported to be reduced when administered together with dexmedetomidine [ 26 ]. A recent study in vivo have showed that a lower loading dose of dexmedetomidine (<10 μg/kg) prevent response to noxious stimulation mainly via enhanced inhibitory postsynaptic transmission within the superficial dorsal horn without altering excitatory synaptic transmission or evoking direct postsynaptic membrane currents.…”
Section: Discussionmentioning
confidence: 99%
“…A wider therapeutic index in sufentanil has been demonstrated compared with other commonly used opioids for PCIA, and sufentanil is not processed into active metabolites [ 24 , 25 ]. Also, the optimal dose of dexmedetomidine combining with sufentanil is vital and clinically the analgesic and sedation is satisfied maximumly, and the consumption of sufentanil is reported to be reduced when administered together with dexmedetomidine [ 26 ]. A recent study in vivo have showed that a lower loading dose of dexmedetomidine (<10 μg/kg) prevent response to noxious stimulation mainly via enhanced inhibitory postsynaptic transmission within the superficial dorsal horn without altering excitatory synaptic transmission or evoking direct postsynaptic membrane currents.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, less opioid was required in the DEX group than the Mg group. Many studies showed that dexmedetomidine reduced opioid ( 9 , 10 , 13 , 14 ) requirements during and after the operation. Dexmedetomidine exerts its analgesic effect through α2 receptors in the locus coeruleus and spinal cord ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…It results in a decrease in heart rate (HR) and cardiac output accordingly ( 11 ), whereas no decrease in stroke volume occurs unless the plasma concentrates reaches above 5.1 µg/mL ( 12 ). This drug also has sedative ( 12 ), amnesic, anxiolytic, hypnotic, and analgesic ( 13 , 14 ) effects with minimal changes in respiratory variables ( 12 , 15 ). Furthermore, it reduces postoperative nausea ( 13 ), vomiting ( 16 ), and shivering ( 17 , 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…DEX, as an adjuvant analgesic, is widely used to improve the patients' pain states, sedation, and sleep quality (13). Recently, DEX was added to opioid-based PCIA and proved to reduce opioids consumption and opioid-related adverse effects, provide stable hemodynamics, and effective postoperative analgesia (14,15). One research studied the optimal dose of DEX combined with SUF in PCIA in patients undergoing spinal surgery.…”
Section: Group Time Cd3 + T(%) Cd4 + T(%) Cd8 + T(%) Cd4 + T/cd8 + T mentioning
confidence: 99%